Disinfection of Ebola Virus in Sterilized Municipal Wastewater. - Kyle Bibby; Robert J Fischer; Leonard W Casson; Nathalia Aquino de Carvalho; Charles N Haas; Vincent J Munster (Public Library of Science (PLoS), 2017)
Concerns have been raised regarding handling of Ebola virus contaminated wastewater, as well as the adequacy of proposed disinfection approaches. In the current study, we investigate the inactivation of Ebola virus in sterilized domestic wastewater utilizing sodium hypochlorite addition and pH adjustment. No viral inactivation was observed in the one-hour tests without sodium hypochlorite addition or pH adjustment. No virus was recovered after 20 seconds (i.e. 4.2 log10 unit inactivation to detection limit) following the addition of 5 and 10 mg L-1 sodium hypochlorite, which resulted in immediate free chlorine residuals of 0.52 and 1.11 mg L-1, respectively. The addition of 1 mg L-1 sodium hypochlorite resulted in an immediate free chlorine residual of 0.16 mg L-1, which inactivated 3.5 log10 units of Ebola virus in 20 seconds. Further inactivation was not evident due to the rapid consumption of the chlorine residual. Elevating the pH to 11.2 was found to significantly increase viral decay over ambient conditions. These results indicate the high susceptibility of the enveloped Ebola virus to disinfection in the presence of free chlorine in municipal wastewater; however, we caution that extension to more complex matrices (e.g. bodily fluids) will require additional verification.